2019
DOI: 10.1002/ange.201911637
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Metastable Pentavalent Plutonium Solid Phase on the Pathway from Aqueous Plutonium(VI) to PuO2 Nanoparticles

Abstract: Here we provide evidence that the formation of PuO2 nanoparticles from oxidized PuVI under alkaline conditions proceeds through the formation of an intermediate PuV solid phase, similar to NH4PuO2CO3, which is stable over a period of several months. For the first time, state‐of‐the‐art experiments at Pu M4 and at L3 absorption edges combined with theoretical calculations unambiguously allow to determine the oxidation state and the local structure of this intermediate phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 34 publications
(48 reference statements)
1
19
0
Order By: Relevance
“…Considering the available experimental data, recorded with high resolution, we find a fairly good agreement in the spectral shape between calculated and measured HERFD spectra for the Th M 4 edge of ThO 2 , 3 for the U M 5 and M 4 edges of UO 2 , 29 and for Np M 5 edge of NpO 2 . 30 However, all of the main structures of the experimental Pu M 5 and M 4 HERFD spectra of PuO 2 5 are reproduced by the crystal-field multiplet calculations; the agreement between calculated and measured spectra becomes somewhat worse than that observed for dioxides of other early actinides. That is because, for PuO 2 , AmO 2 , CmO 2 , BkO 2 , and CfO 2 , the An 5 f -O 2 p charge-transfer effects become significant and must be taken into account in calculations of X-ray spectroscopic data.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Considering the available experimental data, recorded with high resolution, we find a fairly good agreement in the spectral shape between calculated and measured HERFD spectra for the Th M 4 edge of ThO 2 , 3 for the U M 5 and M 4 edges of UO 2 , 29 and for Np M 5 edge of NpO 2 . 30 However, all of the main structures of the experimental Pu M 5 and M 4 HERFD spectra of PuO 2 5 are reproduced by the crystal-field multiplet calculations; the agreement between calculated and measured spectra becomes somewhat worse than that observed for dioxides of other early actinides. That is because, for PuO 2 , AmO 2 , CmO 2 , BkO 2 , and CfO 2 , the An 5 f -O 2 p charge-transfer effects become significant and must be taken into account in calculations of X-ray spectroscopic data.…”
Section: Resultsmentioning
confidence: 95%
“…with much greater capability and efficiency. For example, the long-standing questions, such as about the oxidation path from U(IV) to U(VI) in the U–O system 1 , 4 and possible oxidation of PuO 2 to Pu(V) (see ref ( 5 )) were successfully addressed after the employment of the HERFD-XAS technique.…”
Section: Introductionmentioning
confidence: 99%
“…Synchrotron radiation X-ray techniques, such as X-ray fluorescence (XRF), diffraction (XRD), and absorption spectrometry (XAFS), especially with a submicron beam, provide information on the local molecular speciation (Kelly et al, 2006 ; Kanematsu et al, 2014 ; Smith et al, 2015 ). Recent study of the oxidation state of uranium and the structure of electronic orbitals using resonant inelastic X-ray scattering (RIXS) and HERFD-XANES measurements at the U L III (Kvashnina et al, 2015 ), U M IV (Kvashnina et al, 2013 ; Butorin et al, 2016 ) and Pu edges (Vitova et al, 2017 ; Kvashnina et al, 2019 ) give promising results for future applications. However, a significant limitation of these experimental methods is that the uranium concentrations, even at highly contaminated sites, are often below the detection limits of advanced analytical methods.…”
Section: Uraniummentioning
confidence: 99%
“…Recently, it was found that Pu(IV) stabilization onto mineral surfaces may result in Pu surface precipitation in the form of PuO 2 nanoparticles (Kirsch et al, 2011 ; Romanchuk et al, 2013 , 2016a ; Schmidt et al, 2013 ; Zhao et al, 2016 ) ( Figure 2 ). Therefore, the study of PuO 2 nanoparticles becomes increasingly important, and it is actively being conducted (Powell et al, 2011 ; Romanchuk et al, 2018 ; Kvashnina et al, 2019 ; Gerber et al, 2020 ).…”
Section: Plutoniummentioning
confidence: 99%
“…These observations would not have been possible without the use of X-ray absorption nearedge spectroscopy at the M 4 edge of Pu (compared to the classic but less informative L 3 edge used for actinide samples). This new spectroscopic technique pioneered by Kvashnina et al 16 could help to elucidate new reaction mechanisms for radionuclides, but it also opens the question of the existence of previously unnoticed solid phases.…”
mentioning
confidence: 99%